2013
DOI: 10.1007/s11605-013-2179-4
|View full text |Cite
|
Sign up to set email alerts
|

MRCP is Not a Cost-Effective Strategy in the Management of Silent Common Bile Duct Stones

Abstract: LC with routine IOC is the preferred strategy in a cost-effectiveness analysis of the management of symptomatic cholelithiasis with asymptomatic choledocholithiasis. MRCP was both more costly and less effective under all tested scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…15 Epelboym IL suggested that routine IOC is the preferred strategy in a cost-effectiveness analysis of the management of symptomatic cholelithiasis with asymptomatic choledocholithiasis. 16 MRCP was both more costly and less effective under all tested scenarios.…”
Section: Discussionmentioning
confidence: 94%
“…15 Epelboym IL suggested that routine IOC is the preferred strategy in a cost-effectiveness analysis of the management of symptomatic cholelithiasis with asymptomatic choledocholithiasis. 16 MRCP was both more costly and less effective under all tested scenarios.…”
Section: Discussionmentioning
confidence: 94%
“…But the time component is a universal measure and in the world of shrinking hospital bed availability, is becoming one of our main outcomes measures. Epelboym and colleagues 24 found that MRCP and ERCP were not cost effective strategies for evaluating for suspicion of choledocholithiasis. Laparoscopic cholecystectomy þ IOC was the most cost effective strategy, followed by LC alone.…”
Section: Discussionmentioning
confidence: 99%
“…Their study was not done evaluating specific tools for cost utilization in patients who were admitted with a concern for choledocholithiasis. 24 However, the cost effectiveness of LC þ IOC is prompting us into a paradigm shift in our hospital. Our new protocol ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most important preoperative diagnostic tools are MRC and the traditional ultrasound [31][32][33][34][35] . Alternatively, the policy of routine MRC was not found to be cost-effective in patients without symptoms or suspicion of CBDS, whereas IOC during LC was the best strategy [36] . Interestingly, some authors reported [37] the routine use of IOC during LC, even after MRC and successful preoperative ERCP, to detect residual CBDS.…”
Section: Stonesmentioning
confidence: 99%